2021
DOI: 10.1002/ajmg.a.62162
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the prenatal diagnosis of trisomy 21 show younger maternal age and shift in the distribution of congenital heart disease over a 20‐year period

Abstract: Prenatal testing has changed greatly over the past two decades, which may affect the diagnosis of congenital heart disease (CHD) in Down syndrome. The present study aimed to analyze changes in the prevalence and distribution of CHD diagnosed via ultrasonography and fetopathology in 462 fetuses with trisomy 21 between two consecutive 10‐year periods (1999–2018), as well as the associations between CHDs, ultrasound markers, and extracardiac malformations. Overall, the frequency of cardiovascular malformations in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…A recent Dutch study similarly found the prevalence of atrial septal defect among newborns with Down syndrome to have increased following the introduction of first‐trimester combined screening (FTS) and non‐invasive prenatal testing, but, in contrast, reported the prevalence of AVSD to remain largely unchanged 10 . Potential temporal developments may be due to improved fetal echocardiography; however, a study from Hungary reported an unchanged prenatal detection rate of CHD in trisomy 21 fetuses from 1999–2008 to 2009–2018 11 . No studies have previously investigated the potential impact of prenatal screening and diagnostics on features of the Down syndrome phenotype other than malformations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent Dutch study similarly found the prevalence of atrial septal defect among newborns with Down syndrome to have increased following the introduction of first‐trimester combined screening (FTS) and non‐invasive prenatal testing, but, in contrast, reported the prevalence of AVSD to remain largely unchanged 10 . Potential temporal developments may be due to improved fetal echocardiography; however, a study from Hungary reported an unchanged prenatal detection rate of CHD in trisomy 21 fetuses from 1999–2008 to 2009–2018 11 . No studies have previously investigated the potential impact of prenatal screening and diagnostics on features of the Down syndrome phenotype other than malformations.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Potential temporal developments may be due to improved fetal echocardiography; however, a study from Hungary reported an unchanged prenatal detection rate of CHD in trisomy 21 fetuses from 1999–2008 to 2009–2018. 11 No studies have previously investigated the potential impact of prenatal screening and diagnostics on features of the Down syndrome phenotype other than malformations.…”
Section: Introductionmentioning
confidence: 99%